Pioneer woody species in Leucaena leucocephala and senna siamea hedgerows in a forest ecoysystem in southern Nigeria - Akinnifesi, F.K.; Mutsaers, H.J.W.; Tijani-Eniola, H. (1995)
Floral richness is an important feature of the tropical forest ecosystem. Large numbers of potentially useful volunteer species are usually present in crop fields in traditional farming systems. However; traditional farm lands are undergoing rapid deterioration as a result of increasing population pressure, with the resulting practice of continuous cultivation with little or no fallow. Consequently, many valuable woody species are at the verge of extinction. Work reported in the present study involved the phytosociology of pioneer woody species within hedgerows of Leucaena leucocephala. (Lam.) de Wit and Senna siamea (Irwin & Barnedy) from 16 dispersed farmer-managed alley cropped fields in southwestern Nigeria. The 31 different woody species encountered in the survey had 72.6% similarity coefficient between hedgerows of Leucaena and Senna. Effects of hedgerow species on microsite conditions, and inter-specific associations among volunteer species were discussed in the context of sustainability.